PENINGKATAN SKALA USAHA LEMBAGA KEUANGAN MILIK BUMDES TURI BERKEMBANG DESA TURI PONOROGO MELALUI PENDAMPINGAN MANAJEMEN BERBASIS SYARIAH - Setiawan, Fery; Lailatizzahro, Nisa’u; Ayuningtyas, Angelica Beatris; Trisna, Anita Xtisani; Salsabila, Aghnia Salma (UNIVERSITAS PGRI MADIUN, 2023)
Abstract. The potential of BUMDES Turi is developing well enough to continue to be developed. Organized organization and active participation of the community is the key. One of the BUMDES business units is a Financial Institution whose main activities are savings and services. The research program emphasizes organizational improvement through the development of a sharia-based business scale. The activities are in the form of training, technical guidance and assistance related to the management of financial institutions that run sharia savings and loan businesses. The results obtained are that village financial institution managers have received material on managerial and technical management of Islamic financial institutions, as well as revamping the digital accounting system used. HR has understood the management of financial institutions with the sharia system Abstrak. Potensi BUMDES Turi Berkembang cukup baik untuk terus dikembangkan. Tertatanya organisasi serta peran serta aktif dari masyarakat menjadi kunci. Salah satu unit usaha BUMDES adalah Lembaga Keuangan yang kegiatan utamanya adalah tabungan dan jasa. Pada program Scale Up BUMDES ini tim peneliti melakukan penelitian dengan menekankan pada peningkatan organisasi melalui pengembangan skala usaha berbasis system syariah. Adapun kegiatan berupa pelatihan, bimbingan teknis dan pendampingan terkait pengelolaan Lembaga keuangan yang menjalankan usaha simpan pinjam syariah. Hasil yang didapatkan adalah Pengelola Lembaga keuangan desa telah mendapatkan materi tentang pengelolaan manajerial dan teknis Lembaga keuangan syariah, serta pembenahan system akuntansi digital yang digunakan. SDM telah memahami pengelolaan Lembaga keuangan dengan system syariah.